Evaluation of Treatment with a single (400mg) versus double dose (800mg) of Tocilizumab in Acute Respiratory Distress Syndrome Associated with COVID-19Pneumonia - Mehmet Kabak; Barış Çil (Journal of Contemporary Medicine, 2022)
Background: COVID-19 is a viral infectious caused by novel coronavirus called as severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Recent studies have shown that the level of IL-6 in the severe infection group was higher than that in the moderate group, suggesting that IL-6 can be used as a biomarker for severity assessment. However, the correlation of IL-6 levels in critically ill patients is still unknown. Tocilizumab is a monoclonal antibody against the IL-6 receptor and commonly used for cytokine storm or macrophage activation syndrome (MAS) in COVID-19 patients.